Unrelenting spread of the alien monk parakeet Myiopsitta monachus in Israel. Is it time to sound the alarm? - Postigo, José Luis; Shwartz, A.; Strubbe, D.; Muñoz-Gallego, Antonio Román (Wiley, Society of Chemical Industry, 2017)
Monk parakeets, Myiopsitta monachus Boddaert, are native to South America but have established populations in North America, Europe, Africa and Asia. They are claimed to act as agricultural pests in their native range, and their communal stick nests may damage human infrastructure. Although several monk parakeet populations are present in the Mediterranean Basin and temperate Europe, little empirical data are available on their population size and growth, distribution and potential impact. We investigated the temporal and spatial dynamics of monk parakeets in Israel to assess their invasion success and potential impact on agriculture. Monk parakeet populations are growing exponentially at a higher rate than that reported elsewhere. The current Israeli population of monk parakeets comprises approximately 1500 individuals. The distribution of the species has increased and shifted from predominantly urban areas to agricultural landscapes. In Israel, monk parakeet populations are growing fast and have dispersed rapidly from cities to agricultural areas. At present, reports of agricultural damage are scarce. A complete assessment of possible management strategies is urgently needed before the population becomes too large and widespread to allow for cost-effective mitigation campaigns to be implemented.
Keywords: Periquito monje - Control - Israel; Aves perjudiciales - Control - Israel; Growth rate; Invasive parrot; Israel; Population dynamics; Range expansion